Antidiabetic and antidyslipidemic effects of Ziziphus nummularia leaf and fruit extracts alone and in combination with vildagliptin in alloxan-induced diabetic rats - Pooja Bagdi (Clinical Phytoscience, 2026)
Abstract Background Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycaemia and dyslipidaemia, leading to severe microvascular and macrovascular complications. Although vildagliptin is an effective dipeptidyl peptidase-4 (DPP-4) inhibitor, combination strategies involving medicinal plants may enhance therapeutic efficacy through complementary mechanisms. Ziziphus nummularia has long been used in traditional medicine for diabetes management; however, its potential as an adjunct to DPP-4 inhibitor therapy has not been comprehensively investigated. Objective To evaluate the antihyperglycaemic and antidyslipidaemic effects of hydroalcoholic leaf and fruit extracts of Ziziphus nummularia , administered alone and in combination with vildagliptin, in alloxan-induced diabetic rats. Methods Experimental diabetes was induced in male Wistar albino rats using alloxan monohydrate (150 mg/kg, i.p.). Hydroalcoholic leaf (ZNLE) and fruit (ZNFE) extracts were administered orally at doses of 125, 250, and 500 mg/kg for 28 days. Vildagliptin (0.3 mg/kg) served as the reference drug. Fasting blood glucose and serum lipid profile were analysed using standard biochemical methods. In addition, the antioxidant potential of Ziziphus nummularia extracts was evaluated using in vitro DPPH and superoxide radical scavenging assays, while in vivo antioxidant activity was assessed by measuring superoxide dismutase (SOD) and malondialdehyde (MDA) levels. The extracts were phytochemically characterized using qualitative screening, TLC, HPLC, GC–MS, FTIR, NMR, and quantitative estimation of total phenolic and total flavonoid contents. Results Both extracts significantly reduced fasting blood glucose and improved serum lipid parameters in a dose-dependent manner ( p < 0.001). ZNLE (500 mg/kg) demonstrated greater antihyperglycaemic activity than ZNFE (500 mg/kg). Combination therapy with ZNLE (500 mg/kg) and vildagliptin produced the greatest reduction in fasting blood glucose (68.65%) together with marked improvements in total cholesterol (44.17%), triglycerides (46.87%), LDL cholesterol (56.44%), and HDL cholesterol (140.67%). The extracts demonstrated significant antioxidant activity by increasing SOD levels, reducing MDA levels, and exhibiting concentration-dependent free radical scavenging activity. The combination of the leaf extract with vildagliptin produced the most pronounced antioxidant effect. Conclusion Hydroalcoholic extracts of Ziziphus nummularia exhibited antihyperglycaemic and antidyslipidaemic activities in alloxan-induced diabetic rats. Combination treatment with vildagliptin produced greater improvements in glycaemic and lipid parameters than the corresponding monotherapies; however, formal pharmacological synergy was not evaluated. The findings provide preliminary preclinical evidence supporting further investigation of Z. nummularia extracts, including their combination with conventional antidiabetic treatment, with particular emphasis on mechanistic validation and comprehensive safety assessment. Clinical trial number Not applicable. The overall study workflow and experimental design are illustrated in Graphical Abstract figure.